Competencies and skill development in maternity care services in Victoria - A qualitative study. (August 2019) - Edward, Karen-leigh; Walpole, Lyn; Lambert, Gavin; Phillips, Sarah; Galletti, Alessandra; Morrow, Jane; Gow, Jeffrey; Hiller, Janet
Abstract: In healthcare, continuing professional development is provided to ensure professional standards are maintained and for clinicians to remain fit to practice. The purpose of the study was to identify potential gaps or issues with continuing professional development in maternity services through consultations with key stakeholders and, in addition, to generate possible solutions or recommendations towards the development of a state wide continuing professional development program. The data was collected through semi-structured interviews of a purposive sample between June and August 2018. A thematic analysis was undertaken. Participants included a practicing midwife, allied health practitioner (physiotherapist), manager, healthcare educator, and an outlier service worker (maternal and child health nurse). Following the thematic analysis, four main themes (education, practitioner standards, programme monitoring and resources) were identified along with nine sub-themes. The results suggest organisations need to offer explicit support for staff to access to continuing professional development. In addition, the qualifications of facilitators of continuing professional development and/or consumer education are recommended to go beyond education levels required for registration. In this respect, some organisations credentialed their educators locally in a 'train the trainer' manner however, most participants supported professional preparation for the role of educator. Highlights: Organisations need to offer clear support for staff to access continuing professional development. Continuing professional development facilitators should be credentialled beyond education required for registration. Professional preparation of the clinical educator role is preferred by keystakeholders.